(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Microorganisms isolated from the ocular surface and conjunctiva have been primarily associated with ocular surface diseases such as blepharitis, trachoma, and dry eye syndrome, and have also suggested a role for the ocular and nonocular microbiome in retinal diseases including age-related macular degeneration, glaucoma, uveitis, and diabetic retinopathy. However, relatively little attention is paid to understanding that microorganisms are an integral part of the structure of the eye. Colonizer pioneers interacting with the receptors of eye cells form local immunity, activating pro-inflammatory cytokines. During human ontogenesis, the qualitative and quantitative composition of the ocular microbiome changes depending on the environment. In 2008, when the "human microbiome" project was launched, the eye was excluded from this study due to the low biomass of the environment. The purpose of this review is to summarize current data on the microbiota of the human eye in normal conditions and its changes in ophthalmological diseases. We summarized research results from around the world and found that this contradicts conventional wisdom. So, at first glance, the area for settlement is quite small, however, the ability of microorganisms to form structurally specific colonies, using various adhesive factors, creates not just a surface biofilm, but a unique individual landscape of the eye. However, not all of these microorganisms can be isolated using culture methods, so perhaps this is what influenced the formation of the theory about the low biomass of the eye microbiome. Conclusion: The healthy ocular surface is characterized by a relatively stable microbiome with a relatively low diversity of microorganisms of a certain species. Biofilm landscapes are an integral anatomical unit of the eye, as this structure plays a role in maintaining its homeostasis by activating or inhibiting local cytokines.